2012
DOI: 10.1016/j.cell.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Tet3 CXXC Domain and Dioxygenase Activity Cooperatively Regulate Key Genes for Xenopus Eye and Neural Development

Abstract: SUMMARY Ten-Eleven Translocation (Tet) family of dioxygenases offers a new mechanism for dynamic regulation of DNA methylation and has been implicated in cell lineage differentiation and oncogenesis. Yet their functional roles and mechanisms of action in gene regulation and embryonic development are largely unknown. Here, we report that Xenopus Tet3 plays an essential role in early eye and neural development by directly regulating a set of key developmental genes. Tet3 is an active 5mC hydroxylase regulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
228
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(254 citation statements)
references
References 57 publications
15
228
0
7
Order By: Relevance
“…DNA motif analysis identified a CpG-rich sequence as the highest-ranked motif among Tet3-binding sites (Fig. 2E), also consistent with the previous report (21).…”
Section: Tet3 Regulates the Balance Between Neuroectoderm And Cardiacsupporting
confidence: 79%
See 2 more Smart Citations
“…DNA motif analysis identified a CpG-rich sequence as the highest-ranked motif among Tet3-binding sites (Fig. 2E), also consistent with the previous report (21).…”
Section: Tet3 Regulates the Balance Between Neuroectoderm And Cardiacsupporting
confidence: 79%
“…Tet3-binding sites clustered close to transcription start sites (TSSs), with a low frequency of binding at distal regions relative to the TSSs (Fig. 2D), consistent with a previous report in which Tet3 binding regions were defined by pulldown with a GST fusion of the Tet3 CXXC domain (21). DNA motif analysis identified a CpG-rich sequence as the highest-ranked motif among Tet3-binding sites (Fig.…”
Section: Tet3 Regulates the Balance Between Neuroectoderm And Cardiacsupporting
confidence: 71%
See 1 more Smart Citation
“…3D), although it remains to be determined whether TET3 enhances TRα1-specific enrichment at TRE and/or other genomic sites. In an effort to decipher the underlying mechanism, we demonstrated that the CXXC domain, which mediates TET3 direct binding of genomic DNA (14), is dispensable for stabilization of TRα1 recruitment in chromatin (Fig. S7A).…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of 5hmC into 5fC and/or 5caC, may result in their replacement by cytosine (C) via a base excision repair (BER) demethylation pathway [5]. Work in the frog suggests that the TET3 CXXC domain is critical for its targeting to the promoters of genes that are essential for eye and neural development [7]. Deletion of the CXXC domain from Xenopus laevis Tet3 (xlTET3) abolishes its ability to occupy target gene promoters, thereby preventing the TET3-driven developmental demethylation event that is normally associated with the activation of these genes.…”
mentioning
confidence: 99%